2008
DOI: 10.1111/j.1533-8525.2008.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Contextual Influences of War on Ethnic Prejudice in Croatia

Abstract: This article examines what the determinants of ethnic prejudice in Croatia were in the aftermath of the 1991-1995 war. The analysis is based on a nationwide survey (N = 2,202) conducted in March and April 1996, less than a year after the cessation of war activities in Croatia. The main focus of our analysis is on how war influences the ethnic prejudice of individuals. The influences of individual war-related experiences and the effects of regional differences in the level of war activities are analyzed simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…In Kosovo, war experiences seem to have reduced the trust individuals have in the people in their neighbourhoods (Kijewski and Freitag 2018). Strabac and Ringdal (2008) demonstrated that, while indirect war experiences increased ethnic prejudice in Croatia, direct war experiences did not. Sandovici and Listhaug (2012) found that in Bosnia and Herzegovina direct experiences reduced optimism while indirect experiences increased it.…”
Section: Voters' War Experiences: Combatants Civilians and War Traumamentioning
confidence: 98%
See 3 more Smart Citations
“…In Kosovo, war experiences seem to have reduced the trust individuals have in the people in their neighbourhoods (Kijewski and Freitag 2018). Strabac and Ringdal (2008) demonstrated that, while indirect war experiences increased ethnic prejudice in Croatia, direct war experiences did not. Sandovici and Listhaug (2012) found that in Bosnia and Herzegovina direct experiences reduced optimism while indirect experiences increased it.…”
Section: Voters' War Experiences: Combatants Civilians and War Traumamentioning
confidence: 98%
“…A more fruitful approach has been used in the studies on the consequences of the wars in former Yugoslavia, as well as the conflict between the Israelis and the Palestinians. Here, scholars have usually distinguished veterans from civilians by whether they actually fought in the wars (Massey, Hodson, and Sekulic 2003;Sandovici and Listhaug 2012;Strabac and Ringdal 2008), with some also employing information about the duration of soldiers' service in a combat zone (Grossman et al 2015).…”
Section: Voters' War Experiences: Combatants Civilians and War Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…Simply put, wars change societies. They are also likely to change voters' expectations of what the government should do and their outlook on the social world around them (Strabac and Ringdal, 2008;Hutchison, 2014). Wars also change the real needs of the population -needs that can most often be satisfied only by governmental action.…”
Section: Subnational Elections and Voters' Preferences: Fiscally Libementioning
confidence: 99%